The risk of pediatric cardiovascular diseases in offspring born to mothers with systemic lupus erythematosus: a nationwide study - Cha, Jong Ho; Hwang, Jae Kyoon; Choi, Young-Jin; Na, Jae Yoon (Frontiers in Pediatrics, 2023)
Background: Systemic lupus erythematosus (SLE), a common autoimmune disease predominantly affecting women, has been linked to various complications during pregnancy. The transfer of anti-Ro/SSA antibodies from SLE-affected mothers to their offspring can lead to neonatal lupus and cardiac issues. This study investigates the association between maternal SLE and the risk of pediatric cardiovascular disorders. Methods: The study utilized South Korea's National Health Insurance Service (NHIS) database, covering 3,505,737 children born between 2007-2017 and tracked until 2020. Maternal SLE cases were identified using World Health Organization’s International Classification of Diseases, Tenth revision (ICD-10) codes and linked with delivery records. Cardiologic disorders were categorized into congenital heart disease (CHD), arrhythmic disorders, and acquired heart disease. Propensity score matching with 1:4 ratios were applied to set control group. Results: Among 3,505,737 children, 0.7% (n = 23,330) of children were born from SLE mothers. The incidence of preterm birth was significantly higher in maternal SLE group (5.9% vs. 3.0%). Compared to control group, children born to SLE mothers exhibited significantly elevated risk of overall CHDs (5.5%, adjusted odds ratio (aOR) 1.21; 95% confidence interval (CI) 1.14-1.29)), including atrial septal defect (1.18; 1.09-1.28) and patent ductus arteriosus (1.15; 1.03-1.30). In addition, a notably higher risk was observed in arrhythmic disorders (complete atrioventricular block 7.20; 2.41-21.49), and acquired cardiac disorders, including cardiomyopathy (1.40; 1.17-1.68), and mucocutaneous lymph node syndrome (MCLS) (1.27; 1.15-1.43). Conclusions: Maternal SLE was associated with both congenital and acquired cardiac disorders to offspring, including structural, arrhythmic, and MCLS. This study highlights the need for continuous cardiovascular monitoring from prenatal to pre-adolescent stages in these children due to multifactorial influences involving maternal autoantibodies, genetic predisposition, and environmental factors.